Prioritizing chemicals for developmental neurotoxicity by integrating data from a new approach methods (NAMs) battery covering key cellular events in neurodevelopment - Laura A. Hall; Jui-Hua Hsieh; Skylar W. Marvel; Mamta Behl; Ellen Fritsche; Katharina Koch; Anna Kreutz; Marcel Leist; Arantza Muriana; Timothy J. Shafer; Jason P. Stanko; Robert C. Sills; et al. (NeuroToxicology, 2026)

Regulation of chemicals demands assessment of risks rather than identification of hazards only - P. Marx-Stoelting; V. Ritz; M. Herzler; C. Kneuer; K. Aiello-Holden; S Brescia; S. E. Escher; S. Feustel; E. Fritsche; J. Gebel; E. F. Kenny; R. Landsiedel; et al. (Archives of Toxicology, 2026)
This position paper was collaboratively written during the international expert symposium “EU Chemicals Assessment - Risk- or Hazard-based?” that was organised by the German Federal Institute for Risk Assessment (BfR) in Berlin on November 27th and 28th 2025. Twenty experts from several institutions and European countries considered the scientific merits of both hazard-based and risk-based approaches to chemical safety assessment. While hazard information is essential, it does not reflect real-world exposure conditions that determine the likelihood of harm. On balance, we support a risk-based approach because it enables more proportionate, transparent and scientifically grounded regulatory decisions.

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

Correction: Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2025)

Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2024)
Zinc (Zn) biofortification of rice can address Zn malnutrition in Asia. Identification and introgression of QTLs for grain Zn content and yield (YLD) can improve the efficiency of rice Zn biofortification. In four rice populations we detected 56 QTLs for seven traits by inclusive composite interval mapping (ICIM), and 16 QTLs for two traits (YLD and Zn) by association mapping. The phenotypic variance (PV) varied from 4.5% ( qPN 4.1 ) to 31.7% ( qPH 1.1 ). qDF 1.1 , qDF 7.2 , qDF 8.1 , qPH 1.1 , qPH 7.1 , qPL 1.2 , qPL 9.1, qZn 5.1 , qZn 5.2 , qZn 6.1 and qZn 7.1 were identified in both dry and wet seasons; qZn 5.1 , qZn 5.2 , qZn 5.3, qZn 6.2, qZn 7.1 and qYLD 1.2 were detected by both ICIM and association mapping. qZn 7.1 had the highest PV (17.8%) and additive effect (2.5 ppm). Epistasis and QTL co-locations were also observed for different traits. The multi-trait genomic prediction values were 0.24 and 0.16 for YLD and Zn respectively. qZn 6.2 was co-located with a gene ( OsHMA2 ) involved in Zn transport. These results are useful for Zn biofortificatiton of rice.

Cell division and dynamics in global DNA methylation associated with radicle protrusion in Trichocline catharinensis seeds (Asteraceae) - Ana P. Lando; Daniela Goeten; W. G. Viana; Yohan Fritsche; Miguel P. Guerra; N. Steiner (Acta Physiologiae Plantarum, 2024)

Serendipita restingae sp. nov. (Sebacinales): an orchid mycorrhizal agaricomycete with wide host range - Yohan Fritsche; Morgana E. Lopes; Marc-André Selosse; Valdir M. Stefenon; Miguel P. Guerra (Mycorrhiza, 2021)

Estimation of satellite antenna phase center offsets for Galileo - P. Steigenberger; M. Fritsche; R. Dach; R. Schmid; O. Montenbruck; M. Uhlemann; L. Prange (Journal of Geodesy, 2016)

Reducing the draconitic errors in GNSS geodetic products - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; M. Bloßfeld; M. Fritsche (Journal of Geodesy, 2014)

Low-degree earth deformation from reprocessed GPS observations - Mathias Fritsche; R. Dietrich; A. Rülke; M. Rothacher; P. Steigenberger (GPS Solutions, 2010)

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

Prey capture and accommodation in the sandlance, Limnichthyes fasciatus (Creediidae; Teleostei) - J. D. Pettigrew; S. P. Collin; K. Fritsches (Journal of Comparative Physiology A, 2000)